Establishing duration-specific running intensities from match-play analysis in rugby league - Delaney, J. A.; Scott, T. J.; Thornton, H. R.; Bennett, K. J. M.; Gay, D.; Duthie, G. M.; Dascombe, B. J. (International Journal of Sports Physiology and Performance, 2015)
Rugby league coaches often prescribe training to replicate the demands of competition. The intensities of running drills are often monitored in comparison with absolute match-play measures. Such measures may not be sensitive enough to detect fluctuations in intensity across a match or to differentiate between positions. Purpose: To determine the position- and duration-specific running intensities of rugby league competition, using a moving-average method, for the prescription and monitoring of training. Methods: Data from a 15-Hz global positioning system (GPS) were collected from 32 professional rugby league players across a season. The velocity-time curve was analyzed using a rolling-average method, where maximum values were calculated for 10 different durations, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 min, for each player across each match. Results: There were large differences between the 1- and 2-min rolling averages and all other rolling-average durations. Smaller differences were observed for rolling averages of greater duration. Fullbacks maintained a greater velocity than outside backs and middle and edge forwards over the 1- and 2-min rolling averages (ES 0.8-1.2, P < .05). For rolling averages 3 min and greater, the running demands of the fullbacks were greater than those of the middle forwards and outside backs (ES 1.1-1.4, P < .05). Conclusions: These findings suggest that the running demands of rugby league fluctuate vastly across a match. Fullbacks were the only position to exhibit a greater running intensity than any other position, and therefore training prescription should reflect this.